2013
DOI: 10.1142/s0218271813500740
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Stellar Model Admitting a Quadratic Equation of State

Abstract: A class of solutions describing the interior of a static spherically symmetric compact anisotropic star is reported. The analytic solution has been obtained by utilizing the Finch and Skea (Class. Quant. Grav. 6 (1989) 467) ansatz for the metric potential grr which has a clear geometric interpretation for the associated background spacetime. Based on physical grounds appropriate bounds on the model parameters have been obtained and it has been shown that the model admits an equation of state (EOS) which is qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 44 publications
4
90
0
Order By: Relevance
“…The FinchSkea ansatz has been used by Sharma and Ratanpal (2013) to develop an anisotropic stellar model which has been shown to admit a quadratic EOS. The solution is, in fact, a sub-class of the model developed by Pandya et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The FinchSkea ansatz has been used by Sharma and Ratanpal (2013) to develop an anisotropic stellar model which has been shown to admit a quadratic EOS. The solution is, in fact, a sub-class of the model developed by Pandya et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32], and references therein for an extensive discussion on this point).…”
Section: Introductionmentioning
confidence: 99%
“…Tikekar and Jotania [87,88], Jotania and Tikekar [89] showed that the ansatz suggested by Tikekar and Thomas [90] has these features and the general three-parameter solution based on it also leads to physically plausible relativistic models of strange stars. Several aspects of physical relevance and the maximum mass of class of compact star models, based on Vaidya-Tikekar ansatz, for the both isotropic and anisotropic pressures have been investigated in [53,[91][92][93].…”
Section: Introductionmentioning
confidence: 99%